Uma reflexão sobre a relação da família com a Educação Infantil na escola - Alencar, Rhaissa Alves Cardoso (Universidade Federal do Tocantins, 2020)
This article is a brief reflection on the relationship of family with education, more specifically early childhood education, and has as its theoretical framework authors and legislations that affirm and make crucial discussions about the importance that family and school should go together for formation success of the person. Some of them are: Federal Constitution of Brazil 1988, LDB 1996, Prado (1981), Nogueira (2006), Picanço (2012) and Souza (2009). This paper is divided into discourses on early childhood education with the family, methodological procedures, analysis of field research data and conclusions on the proposed theme and brief suggestions for the improvement of early childhood education with the family, such as: that the family and the school should be aware of and mobilize collective actions to make the child feel safer and more protected during this phase of development.